Augmented Reality (AR) Application Usage Training to Improve Teacher Digital Literacy at SMP Negeri 1 Jeneponto - Riskawati, Riskawati; Baharuddin, Hendra (Jurnal IPMAS, 2023)
SMPN 1 Jeneponto get help a total of 63 Gadget Units (Tablets) brands evercoss from government with goal to get used by internal teachers learning. However Not yet utilized with ok. this because internet network at school the No support and digital literacy teachers greatly low. Solution from problem the is increase teacher 's ability deep digital literacy utilization of Gadgets (Tablets) for learning media both offline and online with implementing Augmented Reality (AR) for optimizing Gadgets (tablets) as learning media in form activity training and mentoring. Activity results training This is there is enhancement about understanding importance teachers' ICT literacy and understanding of AR as a learning medium innovative by 95.6%. Enhancement Teacher's Digital Literacy is 87% and deep teacher skills using AR of 78.2%. This result proves that existing training and mentoring can increase teacher digital literacy at SMP Negeri 1 Jeneponto. Through activity, it is expected that the teachers are up to date on development technology and make an effort to increase one of them is professionalism through understanding Digital Literacy and implementing it in activity learning